WIDE-RANGING VICINITY ALGORITHM FOR SOLVING OPTIMAL REACTIVE POWER PROBLEM - Lenin, K. (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper, Wide-ranging vicinity Algorithm (WVA) is proposed to solve optimal reactive power problem. Wide-ranging vicinity Algorithm equally improves the local & global search. From the global search space a set of arbitrary solutions are primarily generated and then the most excellent solution will give the optimal value. After that, the algorithm will iterate, & there will be two sets of generated solutions in iteration’s, one from the global search space, the other from the set of solutions & it will be produced from the vicinity of the most excellent solution. The proposed Wide-ranging vicinity Algorithm (WVA) has been tested on standard IEEE 118 & practical 191 bus test systems and simulation results show clearly the superior performance of the proposed Wide-ranging vicinity Algorithm (WVA) in reducing the real power loss & voltage profiles are within the limits.